Effectiveness of arbuscular mycorrhizal fungi in increasing growth and yield of maize overlaid on oil palm aged 4 years - Suherman, Cucu; Nurliawati, Sri Desi; Ariyanti, Mira; Dewi, Intan Ratna; Soleh, Mochamad Arief (Kultivasi, 2023)
The intercropping system in oil palm plantations is an effort to optimize land, especially at the immature stages (IS), which have a large open space between the trees, so it can be used for cultivating annual crops such as maize. Oil palm trees are generally planted on marginal lands, such as Inceptisol, which generally lacks in phosphor (P). These problems can be reduced by applying arbuscular mycorrhizal fungi (AMF) to elevate P. This experiment was to determine the dosage and effectiveness of AMF that can improve the growth and yield of maize intercropped with a 4-year-old oil palm. The experiment was conducted at the Ciparanje Experimental Station, Faculty of Agriculture, Universitas Padjadjaran, from February to May 2022. The experiment used a randomized block design (RBD) with six treatments and was repeated four times. The treatment consisted of giving AMF doses, which included: without AMF, 2 g AMF/plant, 4 g AMF/plant, 6 g AMF/plant, 8 g AMF/plant, 10 g AMF/plant. The results showed that the application of AMF can increase growth and better yield maize. A dosage of 10 g AMF/plant is the best treatment, increasing plant height, cob length, cob diameter, dry shelled weight, and 100 seed weight, each 3, 04%, 5.5%, 8.1%, 50.21%, and 8.42% compared to no AMF.Keywords: arbuscular mycorrhizal fungi, intercropping, maize, oil palm